Pastoral resource access and utilization: quantifying the spatial and temporal relationships between livestock mobility, density and biomass availability in southern Kenya - Butt, B. (Wiley, 2010)
The relationships between pastoralists, livestock, and the environment in dryland Africa are complex. Over the last half-century dominant narratives have portrayed pastoralists and their livestock as being responsible for over grazing and degradation without attention to how resource availability and cattle mobility are spatially distributed and temporally variable. The objective of this study is to test hypotheses on the nature, magnitude, and extent of the spatially and temporally explicit interactions between the density and distribution of pastoral cattle and resource availability. The study relies on coupling remotely sensed vegetation indices with cattle Global Positioning Systems (GPS) collar data for a pastoral community in southern Kenya. Data are temporally stratified in order to account for seasonal effects. Across seasons, there is a positive relationship between cattle mobility and resource availability with the trend more pronounced during drier periods, reflecting a strategy of increased resource access. The relationship between cattle density and vegetation reveals a strategy of increased resource utilization during wetter periods. The spatiality of high-density areas differs by season, revealing that cattle intensively utilize different parts of the landscape at different times. Areas closest to the household are consistently impacted by cattle across all seasons. These findings have implications on how the savanna vegetation may be impacted as trends towards sedentarization and reduced pastoral mobility continue.